PENGARUH PEMBERIAN MOTIVASI BELAJAR OLEH GURU, KEMANDIRIAN BELAJAR, DAN PEMANFAATAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR - Erni Zani; I Komang Winatha; Teddy Rusman (JEE (Jurnal Edukasi Ekobis), 2013)
The purpose of this study was to determine the effects of teacher motivation, independent learning and use of instructional media on learning outcomes IPS Integrated semester VIII grade students of SMP N 19 Bandar Lampung. The results:(1)There is a positive and significant effect of motivation to learn by teachers on learning outcomes ips integrated semester eighth grade students of SMP Negeri 19 Bandar Lampung. (2)There is a positive and significant effect on learning outcomes learning independence IPS Integrated Odd Semester eighth grade students of SMP Negeri 19 Bandar Lampung. (3)There is a positive and significant utilization of instructional media on learning outcomes IPS Integrated Odd Semester Class VIII students of SMP Negeri 19 Bandar Lampung. (4)There is a positive and significant effect of motivation to learn by teachers, independent study, and the use of instructional media on learning outcomes IPS Integrated Odd Semester Class VIII students of SMP Negeri 19 Bandar Lampung.Keywords: Giving Motivation By Teacher, Learning Independence, Utilization of Instructional Media, and Learning Outcome